Interrogating My Chandal Life : an Autobiography of a Dalit - Byapari, Manoranjan Mr; Mukherjee, Translator: Sipra Professor (Sage Publications Pvt. Ltd, 2017)
An autobiographical account of struggle from the poorest of the poor to achieve self-respect and win others' respect, against all odds.